Pengaruh Pemikiran Frankfrut School dan Relevansi Pemikirannya dalam Konteks Kontemporer - Saif Arrasid; Widia Lestari; Asri Hasanah; Mardhihah Abbas (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2026)
The Frankfurt School represents one of the most influential traditions of critical thought in the development of twentieth-century social theory and philosophy. This article aims to examine the impact of Frankfurt School thought particularly the ideas of key figures such as Max Horkheimer, Theodor W. Adorno, Herbert Marcuse, and Jürgen Habermas and to analyze the relevance of their ideas within contemporary social contexts. Using a qualitative approach through an extensive literature review, this study examines key concepts such as critical theory, instrumental rationality, and the culture industry, as well as their implications for power relations, advanced capitalism, mass media, and modern democracy. The findings demonstrate that the Frankfurt School’s critique of instrumental rationality and cultural commodification remains highly relevant for understanding contemporary social problems, including digital media dominance, consumerism, and the crisis of the public sphere. This article argues that Frankfurt School thought continues to provide an essential analytical framework for critically engaging with the contradictions of modern and postmodern societies in the era of globalization and digital technology.